Influence of rice husk fillers on mechanical properties of banana/epoxy natural fiber hybrid composites. (2023) - Deepan, S.; Jeyakumar, R.; Mohankumar, V.; Manojkumar, A.
Abstract: Increasing environmental pollution, climate change, and the use of non-biodegradable or renewable resources have become major concerns for researchers in the modern industrialized world. It is believed that if we are to build a sustainable future, we must address these issues while also protecting the capabilities of the forthcoming generations to achieve their own requirements. Compared to synthetic reinforcing fiber natural fiber has different advantages such as harmlessness, low densities, lower processing costs, and similar comparable strength. In this experiment banana fiber reinforced with the epoxy and rice husk bio filler hybrid composites were made and the Mechanical properties of for these hybrid composites were characterized. Different volume fractions of fiber with various composite samples were made by using the traditional hand layup method and pressure applied at moderate temperature. All the hybrid samples were tested under tensile, flexural, and impact loading, the interfaces of fiber matrix were evaluated and the fractured surface structures were analyzed using a Scanning electron microscope (SEM). From the results, it was observed that the composite samples with 30 % banana fibers and 10 % rice husk exhibited better mechanical properties when compared with the other composite compositions.